Realization of Full Control of a Terahertz Wave Using Flexible Metasurfaces. Issue 24 (2nd November 2017) - Zhang, Lei; Zhang, Min; Liang, Huawei
Abstract: Compared with devices controlling microwave and visible light, there is a lack of functional devices for terahertz (THz) wave control. Moreover, the available THz elements are usually manufactured with bulk materials, in contrast to the trend of miniaturization and compact device requirements. Here, full control of both phase and amplitude is achieved experimentally and numerically at 0.14 THz, one of the atmospheric windows, by demonstrating the functionalities such as polarization conversion, metalenses and the generation of a non‐diffraction Airy beam. Significantly, the metal structures are fabricated on a flexible substrate with a total thickness of ≈0.063 l via a standard flexible printed circuit technique. Taking into account the considerable manipulation efficiency and cost‐efficient sample fabrication technique, the results show solid advances in the development of metasurfaces as a versatile platform for designing practical functional devices in the THz range. Abstract : Both power‐efficient and cost‐efficient full control of a terahertz wave is realized using flexible metasurfaces. Samples are easily fabricated via a flexible‐printed‐circuit (FPC) technique on a 100‐µm thick plastic polyimide substrate. Polarization conversion, metalens focusing, and generation of an Airy beam are demonstrated to verify the capability of the flexible metasurfaces.